Upper extremity injuries in gymnasts - Concannon, L. G.; Loveless, M. S.; Matsuwaka, S. T. (Gymnastics medicine - evaluation, management and rehabilitation, 2020)
The upper extremity is subjected to extreme forces in gymnasts. Unlike other sports, gymnastics requires weight-bearing on, landing on, and catching oneself with the upper extremitics. Vaulting and tumbling involve explosive power and weightbearing through the arms. High bar and uncvcn bars generate forces through swinging and catching, parallel bars adds static holds, while rings and pommel horse generale their own unique forces, with extremes of static holds and swinging maneuvers on rings, and extended upper extremity weight-bearing on pommel horse. Most studies of injury epidemiology in gymnastics focus on artistic gymnastics, with very limited data regarding other disciplines. Studies examining both the high school and NCAA injury surveillance Systems have demonstrated that the overall upper extremity injury rate across all sports is approximately 20% . That rate is signilicantly higher in gymnastics, and male gymnasts have a higher incidence of upper extremity injuries than females. In a 2019 systematic review, 42.8% of injuries in male gymnasts were to the upper extremity, compared to 30.8% for females. In females, lower extremity injuries still predominate, at 51% of the total, while they represent only 33% of injuries to males. Within the upper extremity, wrist injuries are most common in females, followed by elbow, while shoulder is most common in males, followed by wrist. The differences in upper extremity injury frequency partially stem from the fact that the three unique events for men (pommel horse, rings, and parallel bars), as well as high bar, are all strictly "arm" events, whereas females only have one "arm" event, uneven bars. Certainly, upper extremity weight-bearing occurs quite significantly on vault, beam, and fioor as well for females, but men also compete in vault and fioor.